The Effectiveness Of Incorporating Interactive Learning Platforms To Programming Lectures (Al-Jabal Journal of Humanities and Applied Sciences, 2024)
Programming is one of the most important aspects of a computing course. Despite the significance of the programming as among core courses in studying computer science, its curriculum hours have been reduced over time in many faculties. Moreover,  some new programming languages need a lot of time to learn and practice , and students do not find time through time of classes ,which compromised the students’ ability to learn and understand . Many studies have shown evidence of progressive interest of computer science students in using Interactive Learning Platform(ILP) in learning programing subjects, however there is still controversy about the positive impact of ILP on student performance and learning. The aim of this study was to investigate the impact and effectiveness of incorporating using ILP to the programming lectures on the performance of the computer science department students in faculty of arts and science Alabyar ,university of Benghazi. The results of this study revealed that students who were given lecture combined with ILP have shown enhancement in performance compared to others who were given ordinary lecture.
Keywords: Computing Course, Interactive Learning Platform(ILP),Programming courses, Programming languages teaching, Programming learning